Polyneuropathy Quality Measurement Set: Quality Improvement in Neurology. (4th January 2022) - Callaghan, Brian C.; Armon, Carmel; Bril, Vera; Colbert, Lindsay; David, William S.; Del Toro, David R.; Fink, Kenneth; Jones, Lyell K.; Kleemeier, Robert; MacGregor, Leslie C.; Bennett, Amy; Shenoy, Anant
Abstract : Peripheral neuropathy affects ∼5% of the population and diabetes is the most common cause. 1 Diabetic neuropathy often leads to pain, but clinicians do not always address neuropathic pain with their patients. 1, 2 Given the effect of painful diabetic neuropathy (PDN) on patients' quality of life, appropriate treatment of this prevalent condition is essential. 1 To increase the delivery of effective management for patients with PDN, the American Academy of Neurology Institute (AANI) published a guideline on the treatment of PDN in 2011, and recently updated this guideline. 1